2020
DOI: 10.1007/s00299-020-02558-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA directed DNA methylation and seed plant genome evolution

Abstract: RNA Directed DNA Methylation (RdDM) is a pathway that mediates de novo DNA methylation, an evolutionary conserved chemical modification of cytosine bases, which exists in living organisms and utilizes small interfering RNA. Plants utilize DNA methylation for transposable element (TE) repression, regulation of gene expression and developmental regulation. TE activity strongly influences genome size and evolution, therefore making DNA methylation a key component in understanding divergence in genome evolution am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Our results show that although the tea plant genome is rich in TEs, the TEs within the tea plant genome were found to be highly methylated. A likely explanation is that the transcriptional suppression of TEs in tea plant by DNA methylation allows them to accumulate high copy numbers with minimal deleterious consequences to the host (Deniz et al, 2019; Wambui Mbichi et al, 2020), which thereby helps to maintain the genomic stability of the tea plant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that although the tea plant genome is rich in TEs, the TEs within the tea plant genome were found to be highly methylated. A likely explanation is that the transcriptional suppression of TEs in tea plant by DNA methylation allows them to accumulate high copy numbers with minimal deleterious consequences to the host (Deniz et al, 2019; Wambui Mbichi et al, 2020), which thereby helps to maintain the genomic stability of the tea plant.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent this threat, DNA methylation mechanisms can be triggered by various mechanisms [ 66 ]. DNA methylation was considered one of the key components in understanding divergence in genome evolution among plants [ 67 ]. The expansion of wheat DMT genes might contribute to the large genome size of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015; Wambui Mbichi et al. , 2020), the features of the regions that overlapped with the 24‐nt siRNA‐covered regions were examined. It was found that over 62% of Fe‐deficiency‐induced hyper CHH‐DMRs overlapped with the 24‐nt siRNA clusters in both roots and shoots (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%